Republic of Armenia : Sixth Reviews Under the Extended Fund Facility Arrangement and the Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses the Republic of Armenia's Sixth reviews under the Extended Fund Facility Arrangement, and the Extended Credit Facility Arrangement. The Central Bank of Armenia has kept the policy rate at 8 percent since 2011, and has narrowed the corridor around the policy rate from 600 to 300 basis points while strengthening fine-tuning operations. Interbank interest rates have become less volatile. External adjustment slowed considerably in 2012, and external vulnerabilities persist. The current account deficit improved by just 0.3 percentage points of GDP as exports, and remittances grew at a healthy pace, as did imports.